The association between 25(OH)D levels, frailty status and obesity indices in older adults - Sousa Santos, AR (2018)
Background Vitamin D deficiency is common in older adults and has been linked with frailty and obesity, but it remains to be studied whether frail obese older adults are at higher risk of vitamin D deficiency. Therefore, the aim of this study is to explore the association between frailty, obesity indices and serum 25(OH)D concentrations. Methods 1447 individuals with 65 years or older, participating in a cross-sectional study (Nutrition UP 65) were included. Frailty, according to Fried etal., body mass index (BMI), waist circumference (WC), body roundness index (BRI) and body shape index (ABSI) were evaluated. A stepwise multinomial logistic regression was carried out to quantify the association between 25(OH)D quartiles and independent variables. Results Median 25(OH)D levels were lower in individuals presenting both frailty and obesity (p<0.001). In the multivariate analysis, pre-frailty (OR: 2.65; 95% CI: 1.63-4.33) and frailty (OR: 3.77; 95% CI: 2.08-6.83) were associated with increased odds of lower 25(OH)D serum levels (first quartile). Regarding obesity indices, the highest categories of BMI (OR: 1.74; 95% CI: 1.06-2.86), WC (OR: 3.46; 95% CI: 1.95-6.15), BRI (OR: 4.35; 95% CI: 2.60-7.29) and ABSI (OR: 3.17 95% CI: 1.86-5.38) were directly associated with lower 25 (OH)D serum levels (first quartile). Conclusions A positive association between frailty or obesity and lower vitamin D levels was found. Moreover, besides BMI and WC, other indicators of body adiposity, such as BRI and ABSI, were associated with lower 25(OH)D serum concentrations.